Labor markets and capital tax competition - Thomas Eichner; Thorsten Upmann (Center for Economic Studies and ifo Institute (CESifo), 2010)
Ogawa et al. (2006) analyze capital tax competition in a fixed-wage approach and show that the original results of Zodrow and Mieszkowski (1986) are not preserved in the presence of unemployment. In the present paper we challenge this view and investigate capital tax competition for some arbitrary institutional setting of the labor market. We find that if the labor market is characterized by some efficient bargaining solution, the results of Zodrow and Mieszkowski (1986) are preserved.
Keywords: H21; J51; 330; capital tax competition; unemployment; efficient bargains; Kapitalertragsteuer; Steuerwettbewerb; Arbeitslosigkeit; Arbeitsmarktflexibilisierung; Lohnverhandlungstheorie; Theorie